2015
DOI: 10.1037/cep0000030
|View full text |Cite
|
Sign up to set email alerts
|

Learning multiple lists at the same time in the Hebb repetition effect.

Abstract: In short-term ordered recall, when 1 list of items is repeated over the course of the experiment, recall performance typically improves. This is known as the Hebb repetition effect (Hebb, 1961). In the present study, we contrasted the typical condition involving a single repeated sequence with concurrent learning of 2 repeated sequences. Participants performed a spatial recall task, in which sequences of 7 dots were presented in each trial. For a given participant, the location of the dots were the same for al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 26 publications
4
16
0
Order By: Relevance
“…As currently formulated, both models learn only from presentation and not from recall. Saint-Aubin, Guérard, Fiset, and Losier ( 2015 ) described how both models are also capable of learning more than one list at a time. Indeed, Page and Norris ( 2009 ) presented simulations of learning two lists.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As currently formulated, both models learn only from presentation and not from recall. Saint-Aubin, Guérard, Fiset, and Losier ( 2015 ) described how both models are also capable of learning more than one list at a time. Indeed, Page and Norris ( 2009 ) presented simulations of learning two lists.…”
Section: Resultsmentioning
confidence: 99%
“…This ensured that comparisons between the sequences at different stages of learning were not confounded with time. Existing data had indicated that participants have little difficulty in learning two lists simultaneously, even when those lists are constructed by permuting the same set of items (Kalm, Davis, & Norris, 2013 ; Saint-Aubin, Guérard, Fiset, & Losier, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…Namely, although the Hebb and the Filler sequences were still interleaved, there was only one Filler sequence following two successive but distinct Hebb sequences, each containing different sequences of syllables. Previous studies have demonstrated successful concurrent learning of several different Hebb sequences (Page, Cumming, Norris, McNeil, & Hitch, 2013;Saint-Aubin, Guérard, Fiset, & Losier, 2015). As a result, the order of the presentation of Hebb and Filler trials was: Hebb sequence 1, Hebb sequence 2, Filler sequence.…”
Section: Experiments 3 Methodsmentioning
confidence: 98%
“…For example, most experiments using the Hebb repetition task used digits (Cumming, Page, & Norris, 2003;Oberauer & Meyer, 2009), letters (Cunningham et al, 1984;Kalm & Norris, 2016), words (Page et al, 2006;Page et al, 2013), or pictures of well-known objects (Mosse & Jarrold, 2008) as stimuli. Moreover, although language learning implies the auditory perception and a verbal production of words, most studies departed from the natural context of language learning by using visually presented sequences (Saint-Aubin, Guérard, Fiset, & Losier, 2015;Szmalec et al, 2009) or written recall (Hitch et al, 2009;Oberauer & Meyer, 2009;Page et al, 2013). Finally, previous studies with verbal materials had minimized the overlap between the repeated list and the nonrepeated lists (Hitch et al, 2009;Page et al, 2013), whereas words from all languages are made from a limited set of phonemes.…”
mentioning
confidence: 99%